DINAMIKA STUDI TAFSIR DI PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI (PTKIN), INDONESIA - Tamrin, Darlis dan (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2024)
The study of TafsIr in State Islamic Religious Higher Education (PTKIN) has an important role in enriching the treasures and development of contemporary Al-Qur'an studies. Therefore, this article aims to discuss the dynamics of tafsir studies at IAIN Palu (currently Datokarama State Islamic University Palu) as a center for Al-Qur'an studies for the people of Central Sulawesi in general and Palu City in particular. Apart from that, this research aims to map the study of the Al-Qur'an at IAIN Palu which is a reference for interpreters of the Al-Qur'an in Indonesia and discuss the uniqueness of the Al-Qur'an discourse at IAIN Palu as one of the determining factors in the accreditation process. For this reason, I analyzed the method and context of academic exegesis in the form of student theses (2013-2017) and IAIN Palu lecture articles published in the IAIN Palu internal journal 2005-2017. The results of the study and investigation concluded that the dynamics of academic exegesis studies at IAIN Palu had a classical and modern thematic pattern with a tendency for the context of studies to be conducted more on contemporary social issues, especially up to 2015. In 2016, student and lecturer studies directed the study of the living Qur'an. an as one of the new trends in contemporary Al-Qur'an studies. This research confirms that the study of interpretation at IAIN Palu has experienced quite dynamic development as many new lecturers introduce various interpretation paradigms that are more contextual and progressive.